Chemotaxis Away from 4-Chloro-2-nitrophenol, 4-Nitrophenol, and 2,6-Dichloro-4-nitrophenol by Bacillus subtilis PA-2 - Pankaj Kumar Arora; Mi-Jeong Jeong; Hanhong Bae (Journal of Chemistry)
Bacterial strain PA-2 exhibits chemotaxis away from 4-chloro-2-nitrophenol, 4-nitrophenol, and 2,6-dichloro-4-nitrophenol. This strain was identified as Bacillus subtilis on the basis of the 16S rRNA gene sequencing. The drop plate assay and the chemical-in-plug method were used to demonstrate negative chemotactic behavior of strain PA-2. The growth studies showed that strain PA-2 did not utilize 4-chloro-2-nitrophenol, 4-nitrophenol, and 2,6-dichloro-4-nitrophenol as its sole sources of carbon and energy. This is the first report of negative chemotaxis of 4-chloro-2-nitrophenol, 4-nitrophenol, and 2,6-dichloro-4-nitrophenol by any bacterium.